1983
DOI: 10.1002/esp.3290080506
|View full text |Cite
|
Sign up to set email alerts
|

Suspended sediment in rapid subsurface stormflow on a large field plot

Abstract: The occurrence of rapid movement of suspended sediment in subsurface stormflow on a large field plot in California is described. Concentrations of over 1OOOmg I-' were recorded in storms of only low to moderate intensity. The observed sediment was composed of uniformly fine-sized particles 4 to 8 pm in diameter. The mode of transport seems different from processes previously reported. Differences in sediment concentrations in different events, levels of 37Cs on the sediment, and several other types ofevidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Deasy et al, 2009;Russell et al, 2001). Sub-surface particulate fluxes are likely to occur following soil pipe erosion (Verachtert et al, 2011), or detachment at the surface by raindrop impact which is subsequently delivered through soil macro-pores or sub-surface drains (Pilgrim and Huff, 1983). Although these sub-surface processes may be important during low magnitude events, as storm intensity increases, additional pathways of sediment movement become progressively important (Sayer et al, 2006), limiting the occurrence of anti-clockwise hysteresis events to low magnitude runoff events.…”
Section: Of-eight Hysteresis With An Anti-clockwise Loop (A8) This Imentioning
confidence: 99%
“…Deasy et al, 2009;Russell et al, 2001). Sub-surface particulate fluxes are likely to occur following soil pipe erosion (Verachtert et al, 2011), or detachment at the surface by raindrop impact which is subsequently delivered through soil macro-pores or sub-surface drains (Pilgrim and Huff, 1983). Although these sub-surface processes may be important during low magnitude events, as storm intensity increases, additional pathways of sediment movement become progressively important (Sayer et al, 2006), limiting the occurrence of anti-clockwise hysteresis events to low magnitude runoff events.…”
Section: Of-eight Hysteresis With An Anti-clockwise Loop (A8) This Imentioning
confidence: 99%
“…The rapid transport of particles to depth depends on the structure of the soil, particularly on the presence of vertical continuous macropores. Pilgrim and Huff (1983), Jacobsen et al (1997), Laegdsmand et al (1999), Laubel et al (1999), and McKay et al (2000) observed rapid breakthrough of colloidal particles involving preferential flow. Pilgrim and Huff (1983) as well as Hardy et al (2000) suggested that the particles were detached at or near the soil surface by raindrop impact and that subsurface flow subsequently carried the particles primarily through soil macropores.…”
mentioning
confidence: 97%
“…Pilgrim and Huff (1983) found suspendedsediment concentrations greater than 1,000 milligrams per liter in subsurface flow through soil macropores. The ability of flow into the bed to transport fine particles is an important factor in determining the vertical distribution of fine material below the active bed.…”
Section: Particle Strainingmentioning
confidence: 91%